Erratum - Chen, Jieh-Haur; Ong, Chuan Fang; Zheng, Linzi; Hsu, Shu-Chien (International Journal of Strategic Property Management, 2017)
Erratum. International Journal of Strategic Property Management, 21(4), p. 417